Sodium channel antagonists for the treatment of migraine. (August 2014) - Chiossi, Lorenza; Negro, Andrea; Capi, Matilde; Lionetto, Luana; Martelletti, Paolo
<x xml:space="preserve">Abstract</x> Introduction: Migraine has a strong social impact, influencing both quality of life and work productivity. Therapeutic approach of migraine consists of a multimodal program of pharmacotherapy and behavioral therapy in order to reduce the risk of chronification. Indications for the use of preventive therapy are three or more attacks per month, significant disability, attack duration that is > 90 min. Areas covered: In this review, studies conducted on sodium channel antagonists for the prophylaxis of migraine are selected using the International Classification of Headache Disorders (ICHD)-I and -II diagnostic criteria for migraine and are open-label and placebo-controlled studies. Expert opinion: Several sodium channel antagonists, such as valproic acid, topiramate, lamotrigine, zonisamide, carbamazepine and oxcarbazepine, are widely used in migraine although without similar level of efficacy. Among these antiepileptic drugs, valproic acid and topiramate seem to be more effective in migraine, as reported in the majority of controlled studies. In spite of their high efficacy rate, important side effects should be always monitored, especially depression, cognitive functions, weight gain, sleepiness and dizziness. The usefulness of this class drug will be dramatically improved by using ongoing data on individual pharmacogenomics profile.